The early development of the aviation industry : entrepreneurs of the sky - Abbott, Malcolm, 1963-; Bamforth, C.J. (New York, NY : Routledge, 2019)
The Early Development of the Aviation Industry: Entrepreneurs of the Sky provides an introduction to the world of the early aviation industry and the business endeavours of the original aviators. Many of the firstpioneers who flew heavier-than-air planes went on to develop considerable industrial concerns. In doing so they exhibited a number of entrepreneurial qualities, which provide useful case studies for those interested in studying how successful entrepreneurs create or develop opportunities at the inception and emergence of high-tech industries. This book looks at the careers of pioneer aviators in the United States, Britain and France such as A.V. Roe, Thomas Sopwith, Glenn Curtiss and William Boeing. It examines this group of entrepreneurs during the start-up and early development stages of an emerging industry undergoing considerable technological change, and relates this experience to contemporary studies and experiences of entrepreneurship. The book explores what made these men successful in their entrepreneurial endeavours to help promote a better understanding of what makes an entrepreneur and what business and economic conditions are needed to allow such men to be successful. This book makes a major contribution to our knowledge of the development of the twentieth century economy and is essential reading for students and academics who are interested in the development of aviation and the nature of entrepreneurial behaviour.
OCLC-licensed vendor bibliographic record.
Keywords: Aircraft industry -- History; Aircraft industry -- United States -- History; BUSINESS & ECONOMICS / Industries / General; TRANSPORTATION / Aviation / Commercial; TRANSPORTATION / Aviation / History